Perkembangan Strategi Pemasaran dalam Industri Jasa - Iqbal, M. Ali (Jurnal Ekonomi : Journal of Economic, 2013)
AbstractThe marketing strategy in service industry is very important since the growing rapidly service industry in the recent years. The development the marketing strategy in service industry has changed from year to year. Drawing on insight from extant literature this article purpose analysis of the development marketing strategy in service industry. The qualitative research is used in this study by using several literatures. The author found that there was a change inÂ  marketing strategy in service industry. The triangle model of marketing service has changed to become triangle model with technology as know asÂ  self service technology.Keywords: services strategy, self services technology, service industryAbstrakStrategi pemasaran dalam industry jasa sangat berperan penting sejak bertumbuhnya industry jasa belakangan ini. Pengembangan strategi pemasaran industry jasa telah berubah dari tahun ke tahun. Dengan menggunakan kajian beberapa beberapa literature artikel ini bertujuan untuk melakukan analisis terhadap perkembangan strategi pemasaran di dalam industry jasa. Penelitian kualitatif digunakan pada studi ini dengan menggunakan literature-literatur ilmiah. Penulis menemukan bahwa telah terjadi pergeseran strategi pemasaran di dalam industry jasa. Model â€œtriangleâ€ dalam industry jasa telah berubah menjadi model â€œtriangleâ€ dengan menggunakan teknologi yang kita kenal dengan teknologo pelayanan sendiri.Kata kunci: strategi pelayanan, teknologi pelayanan, service industri